Association of Tuberculosis and Infections of Herpes Simplex, Varicella Zoster Viruses and Cytomegalovirus - A. S. Kazanova; V. F. Lavrov; A. V. Panteleev; I. V. Lyadova (Эпидемиология и вакцинопрофилактика, 2015)
To determine frequency of Herpes simplex (HSV), Varicella zoster viral (VZV) and Сytomegaloviral (CMV) coinfection with tuberculosis (TB) we examined 45 patients with pulmonary TB and 62 healthy donors, 25 of them were healthcare workers in tuberculosis hospital and the rest 37 had no previous contact with TB. None of the participants had vesicular rash of skin or mucosa. For diagnosis of herpes viral infection enzyme-linked immunosorbent assay for detection of HSV, VZV, CMV IgG in PBMC supernatants was performed. A significant increase in CMV (53.3%) and HSV (40%) infection in TB patients was observed comparing to healthy donors (p < 0.05; 19.4 and 16.1% respectively). Frequency of VZV infection in TB patients (17.8%) and healthy donors (8.1%) differed statistically unsignificantly. Levels of specific IgG secretion in PBMC culture in both groups in case of VZV and CMV infections didn’t differ, but in case of HSV coinfection in TB patients mean level of HSV IgG secretion (1.106 ± 0.297 OD) significantly exceeded mean level of HSV IgG in PBMC supernatants of healthy donors with asymptomatic HSV infection (0.285 ± 0.048 OD, р < 0,05). The obtained data give evidence of an association of pulmonary TB and herpes viral infections. Influence of these coinfections on course and morbidity of TB requires further research.